PELATIHAN KEGIATAN MENGGUNTING DAN MENEMPEL UNTUK MENINGKATKAN PERKEMBANGAN MOTORIK HALUS KELOMPOK A DI TK NEGERI SATU ATAP KEMBAYAN - Sarayati Sarayati; Sudarto Sudarto (STKIP Persada Khatulistiwa Sintang, 2025)
Abstract: The purpose of this Community Service (PkM) activity is to provide knowledge and understanding through cutting and pasting activities to improve the fine motor development of group A children of Kindergarten Negeri Satu Kembayan as a learning medium. This cutting and pasting activity is carried out in kindergarten because it will lead to direct practice, this activity can stimulate aspects of child development, namely cognitive, fine motor, and social emotional aspects. The method used in this community service activity is the training method. The training was carried out through collaboration between the community service team, students, and teachers of the One Roof Kindergarten in Kembayan, Kembayan District. In its implementation, this program went through 3 stages of activities, namely the planning stage, the implementation stage, and the evaluation stage. The results of this Community Service activity were that the students looked enthusiastic about being able to carry out cutting and pasting activities and they were able to carry out all stages of the activity well, starting from recognizing pictures, letters, and cutting and pasting, washing hands, and evaluating the media making activity.